Session RPE during prolonged exercise training - Fusco, A.; Knutson, C.; King, C.; Mikat, R. P.; Porcari, J. P.; Cortis, C.; Foster, C. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Although the session rating of perceived exertion (sRPE) is primarily a marker of internal training load (TL), it may be sensitive to external TL determining factors, such as duration and volume. Thus, sRPE could provide further information on accumulated fatigue not available from markers of internal TL. Therefore, the purpose of this study was to investigate sRPE during heavy training bouts at relatively constant intensity. Methods: Eleven university swimmers performed a high-volume training session consisting of 4×10×100-yd (4×10×91.4 m). Repetition lap time and heart rate were measured for each repetition and averaged for each set. Blood lactate concentration was measured after each set. At the end of each set, a 10-minute rest period was allowed, during which sRPE values were obtained, as if the training bout had ended. Results: There were no differences between sets for lap time (P=.096), heart rate (P=.717), and blood lactate concentration (P=.466), suggesting that the subjects were working at the same external and internal intensity. There was an increase (P=.0002) in sRPE between sets (first 4 [1.2], second 5 [1.3], third 7 [1.3], and fourth 8 [1.5]), suggesting that even when maintaining the same intensity, the perception of the entire workload increased with duration. Conclusions: Increases in duration, although performed with a consistent internal and external intensity, influences sRPE. These findings support the concept that sRPE may provide additional information on accumulated fatigue not available from other markers of TL.